Resolution of N-Protected amino alcohols by porcine pancreatic lipase - Magrioti, V.; Fotakopoulou, I.; Athinaios, N.; Anastasopoulou, P.; Constantinou-Kokotou, V.; Kokotos, G. (Letters in Organic Chemistry, 2010)
The resolution of 2-amino alcohols protected by urethane-type groups either via porcine pancreatic lipase (PPL) hydrolysis of the corresponding racemic acetates or via PPL catalyzed transesterification of racemic alcohols was studied. In both cases, Boc protecting group led to better chemical yields and enantiopurities than Z and Fmoc protecting groups. Furthermore, a simple and efficient method for the synthesis of the medicinally interesting optically pure (R)-2-aminohexadecanol was developed.